(untitled) (Jurnal Bina Praja, 2021)
On December 9, 2020, The Sleman Regional Head Election was won by the Kustini-Danang pair. The victory of Kustini (wife of Sri Purnomo, the incumbent Regent) is referred to as part of kinship politics. Kinship politics is understood as an attempt to perpetuate power, in this case, Sri Purnomo’s power. Sri Purnomo itself is the Regent of Sleman who is famous for his political superiority, which is shown by winning two consecutive terms. This study aims to capture the local political phenomenon in Sleman by identifying the political contestation in the 2020 Regional Head Election from a socio-historical and some political momentum that occurred during the Sri Purnomo regime. To further explore the phenomenon of kinship politics in Sleman Regency, this study used a qualitative approach and used two main data search methods: primary data and secondary data. The results showed that Sri Purnomo has high superiority in his leadership. Sri Purnomo transformed into a local strongman with the support of some local elite networks he had built. As the local strongmen, he formed political alliances that had high loyalty based on patron-client relationships. In the end, by presenting his wife, Kustini Sri Purnomo as his successor, it shows that the politics of kinship are nothing more than an extension of the hand to continue Sri Purnomo’s power.